2000
DOI: 10.1590/s0100-204x2000000400024
|View full text |Cite
|
Sign up to set email alerts
|

Degradação de 14C-atrazina em solo sob condições semicontroladas

Abstract: Objetivou-se neste trabalho, avaliar a mineralização e a formação de resíduos extraível e não-extraível de 14C-atrazina em um solo intensivamente utilizado para fins agrícolas no Estado de São Paulo. Atrazina radiomarcada foi aplicada (5 L ha-1 ou 2 mg kg-1 de i.a.) em um Latossolo Vermelho-Escuro, álico, A moderado, textura média. Frascos erlenmeyer contendo 200 g (peso seco) do solo assim preparado e com umidade ajustada para 2/3 da capacidade de campo foram enterrados na Estação Experimental de Lisímetros d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The data also indicated that initially the number of atrazine‐degrading microorganisms in soil with a 10‐yr history of atrazine application (G soil) was not as high as it was in soil with 40‐yr history of application (MP soil), suggesting that the proportion of microorganisms capable of degrading atrazine was dose‐dependent and therefore increased with continued annual application of the same herbicide (Barriuso and Houot, 1996; Ghani et al, 1996; Sparling et al, 1998; Abdelhafid et al, 2000a, 2000b). The low activity of atrazine degraders during the 2 to 12 (MP soil) or 6 to 12 (G soil) weeks of incubation (stationary phase) can be attributed to the lack of nutrients and/or herbicide in the available fraction (Queiroz and Monteiro, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data also indicated that initially the number of atrazine‐degrading microorganisms in soil with a 10‐yr history of atrazine application (G soil) was not as high as it was in soil with 40‐yr history of application (MP soil), suggesting that the proportion of microorganisms capable of degrading atrazine was dose‐dependent and therefore increased with continued annual application of the same herbicide (Barriuso and Houot, 1996; Ghani et al, 1996; Sparling et al, 1998; Abdelhafid et al, 2000a, 2000b). The low activity of atrazine degraders during the 2 to 12 (MP soil) or 6 to 12 (G soil) weeks of incubation (stationary phase) can be attributed to the lack of nutrients and/or herbicide in the available fraction (Queiroz and Monteiro, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Atrazine degradation in soils occurs both via chemical and biological processes, resulting in the formation of metabolites such as hydroxyatrazine (2‐hydroxy‐4‐ethylamino‐6‐isopropylamino‐ s ‐triazine), deethylatrazine (2‐amino‐4‐chloro‐6‐isopropylamino‐ s ‐triazine), and deisopropylatrazine (2‐amino‐4‐chloro‐6‐ethylamino‐ s ‐triazine), which have a different mobility and toxicity than atrazine and hence also different contaminant potential (Barrett, 1996). Chemical dechloration (hydroxyatrazine) dominates in some soils, particularly those showing low pH (Peixoto et al, 2000; Queiroz and Monteiro, 2000), whereas in other soils microbial breakdown is the main decomposition pathway with formation of dealkylated metabolites (deethylatrazine and deisopropylatrazine) and ring cleavage (Kaufman and Kearney, 1970; Barriuso and Houot, 1996; Abdelhafid et al, 2000a, 2000b). Formation of non‐extractable or bound residues also constitutes a very important mechanism for the attenuation of the atrazine, which is associated with the soil organic matter content (Capriel et al, 1985; Peixoto et al, 2000).…”
mentioning
confidence: 99%